Evaluating policy options for the mandarin orange industry in indonesia using system dynamics framework - Mufidah, Lyli (2016)
The mandarin orange industry is one of the important fruit sectors in Indonesia. This industry shows a benefit over cost ratio of 1.8 in medium scale cultivation, suggesting a higher economic return. The average annual rate of growth is 25% between 1999 to 2007. However, after 2007 to 2012 there was a significant decline from 2.5 million tonnes to 1.4 million tonnes. This makes the local production’s ability to meet mandarin orange consumption reduced from 98% in 1999 to 92% in 2012; while, the gap was fulfilled by imports. The increase of mandarin orange imports from 27 thousand tonnes to 179 million tonnes from 1999 to 2012 became a government concern. The government tried to give a stimulus to the local production by issuing protection policies. These interventions will make a change in the mandarin orange industry landscape. The general objective of this study is to evaluate the market protection policies on mandarin orange industry in Indonesia using system dynamics framework. The specific objectives are: (i) to examine the relationship between structure and behavior of the mandarin orange industry in Indonesia, (ii) to assess the impact of the protection policies on the local production and consumption, and (iii) to simulate the impact of changes in policy scenarios on the mandarin orange industry. A mandarin orange system dynamics model was developed to study and understand the behavior of the mandarin orange industry. The system dynamics methodology was used because of its ability to accommodate causal relationships, non linearity and delays that exist in the Indonesian mandarin orange industry. The model was divided into two main sectors; they were the local and imported mandarin oranges. Each had production and consumption sub models as inflow and outflow rates. The study also identified four policy frameworks: the domestic protection policy, stimulus policy, R&D policy and disease management that includes funding and the improvement of extension agent ratio that decanted into six scenarios. Scenario 1 (S1): referred to “business as usual” (BAU) scenario, where only the domestic protection policy was applied; Scenario 2 (S2): the stimulus strategy was added to the policy; Scenario 3 (S3): combination of S2 with R&D policy; Scenario 4 (S4) was a combination of S3 with disease management, including fund and improvement extension agent-area ratio; Scenario 5 (S5): introduced free market situation where no protection policies were applied; and Scenario 6 (S6): free market was supported with R&D and disease management, including fund and improvement extension agent-area ratio. The results showed that S4 was the best policy alternative, where it was estimated that the production of oranges may reached 2.9 million tonnes in 2034, relative price value of 0.8, expected profit of Rp18.638,00/kg and reduction in imports to 43 thousand tonnes. S6 showed that the removal of the protection policy, supported by R&D and disease management still increase production to 2.5 million tonnes, relative price 0.77, expected profit Rp12.623,00/kg and make import lower than BAU with the value of 215 thousand tonnes. This suggests that the protection policy can be gradually reduced as under an open market the mandarin industry would gain competitiveness through a strong support of R&D and technology adaption through extension agents and effect of disease management.